2019
DOI: 10.1186/s12909-019-1617-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring change in knowledge acquisition of Rwandan residents: using the American Board of Pediatrics International In-Training Examination (I-ITE) as an independent tool to monitor individual and departmental improvements during the Human Resources for Health program: an observational study

Abstract: Background Rwanda is the only African country to use the pediatric International In-Training Examination (I-ITE). The objectives of this study were to use the scores from the I-ITE to outline the baseline level of knowledge of Rwandan residents entering the pediatric residency and the trends in knowledge acquisition from 2012 to 2018, during the Human Resources for Health (HRH) Program, an education partnership between the Rwanda Ministry of Health and a consortium of US universities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We sought to gain a rich and detailed understanding of the experiences, attitudes and perceptions of the residents, and for the results to emerge from the data. Our previous paper has demonstrated that the I-ITE exam is a valuable tool to measure knowledge acquisition in Rwandan residents 5 , whereas this current paper, using qualitative methods, gave the opportunity to understand the residents' experience and the cultural relevance to them as end-users.…”
Section: Why Was a Mixed-methods Approach Taken?mentioning
confidence: 96%
See 3 more Smart Citations
“…We sought to gain a rich and detailed understanding of the experiences, attitudes and perceptions of the residents, and for the results to emerge from the data. Our previous paper has demonstrated that the I-ITE exam is a valuable tool to measure knowledge acquisition in Rwandan residents 5 , whereas this current paper, using qualitative methods, gave the opportunity to understand the residents' experience and the cultural relevance to them as end-users.…”
Section: Why Was a Mixed-methods Approach Taken?mentioning
confidence: 96%
“…In Rwanda, there is a single pediatric residency program graduating approximately five to 18 pediatricians per year. Rwanda is the first sub-Saharan nation to employ the pediatric I-ITE to provide formative feedback to individual residents and to give feedback to the faculty on the overall performance of residents within the residency program 5 . The I-ITE, however, is a formative assessment based on the American ITE examination, and though adapted it is being utilised in a very different cultural and medical context in terms of both the populations, patients and pathologies encountered, but also in respect to the language skills, learning styles and asseessment experience of the residents undertaking the assessment.…”
Section: Pediatric Residency In Rwandamentioning
confidence: 99%
See 2 more Smart Citations
“…The PI had not previously undertaken qualitative research and was therefore supported by a faculty member (PC) experienced in qualitative research. PC supervised and co-authored the work and is a male medical doctor trained in the United Kingdom, and at the time of the study was an associate professor in pediatrics at Yale University, USA, working on the Human Resources to Health Programme in Rwanda [ 37 , 38 ]. PC has received training in qualitative methods during his Masters in Child Health and has contributed to previous qualitative research in Rwanda (Yale) and the United Kingdom (UoL).…”
Section: Methodsmentioning
confidence: 99%